Who was who in world exploration - Carl Waldman (Facts on File, 1992)
From Henry L. Abbott to Lavrenty Alekseyevich Zagoskin, the book is the most comprehensive survey of the lives, expeditions and significant contributions of more than 800 explorers from around the world. Uncovering a wealth of previously unknown facts and tidbits on renowned international figures, such as Roald Amundsen, Daniel Boone, Christopher Columbus, Ferdinand Magellan and Marco Polo, the book also brings to light the accomplishments of hundreds of lesser-known explorers, including: Edward Eyre, Freydis, Mary Kingsley, Pliny de Elder, Annie Taylor. Each exhaustively researched entry contains: birth and death dates, nationality, occupation, capsule chronology of voyages, complete biographical data, description of expeditions. With more than 120 black-and-white illustrations and period maps, 15 original maps, an appendix of explorers by region and a bibliography, the book is a must for exploration scholars and buffs